O relacionamento entre qualidade em serviços, valor percebido, imagem corporativa e seus impactos na satisfação de clientes bancários - Favoretto, Camila (2017)
The service sector has gained prominence both in the Brazilian and in the world’s economies, impelling organizations to seek excellence in their service. Faced with this need, in the banking sector, institutions have emphasized a mutually beneficial relationship with their clients, in order to make the management of services a competitive differential. Service quality and customer satisfaction have been identified as key factors for competitiveness and customer retention. In this context, there is a challenge in understanding the relationships among the antecedent factors of customer satisfaction. In fact, previous research agrees neither on the direction nor on the degree of relationship of these factors, besides being studied in different countries and service sectors. Thus, the purpose of this study is to investigate the multiple relationships among the constructs – service quality, perceived value, corporate image and customer satisfaction. For that, a literature review was carried out on the concepts pertinent to this research; the constructs were conceptualized individually, providing the theoretical basis for their operationalization. Then, the relations among them were evidenced by the statement of hypothetical links, thus specifying the theoretical model. After articulating the knowledge in a theoretical manner, in the city of Sorocaba-SP, a survey was conducted, using a questionnaire randomly applied to 136 clients of the banking services, which use at least one of the five largest Brazilian banks. Data analysis was performed through the structural equation modeling technique, in order to test the consistency of the hypotheses and to identify the direction of the relations. The results showed that service quality directly influences the perceived value and the corporate image and that the image directly impacts customer satisfaction, making it a potential mediating variable for the quality-satisfaction relationship. The direct relationship between quality and satisfaction as well as perceived value and satisfaction were not observed, considering the sample of this research and the levels of significance. Therefore, this study might be both theoretically and practically relevant. Such knowledge directs banking institutions to prioritize the allocation of resources and efforts on the corporate image. Through this factor, the expected implications related to customer satisfaction will be achieved directly. Simultaneously, banks must acknowledge that the delivery of high quality is an important driver of corporate image and perceived value. In the academic field, the study develops architecture of measurable indicators making it possible to evaluate the proposed constructs, besides constructing an explanatory theory in the understanding of the relations among them for the banking sector.